Social Equity Dimensions of Flood Risk Management in Canada - Chakraborty, Liton (University of Waterloo, 2021)
Disproportionate exposure to hazards among socioeconomically disadvantaged populations and racial/ethnic minority communities contributes to rising environmental injustices worldwide. Examining the link between race/ethnicity, socioeconomic status, and the location of environmental hazards provides an important foundation for understanding fundamental determinants of environmental inequities based on socioeconomic indicators and disparate impacts of hazards. To date, Canada’s environmental justice (EJ) research has focused on identifying vegetation, air pollution, health, and noise-related environmental inequities, mostly in a few selected cities and metropolitan areas. This is inadequate for a national policy conversation on environmental injustices. Although flooding has emerged as the costliest and most frequently occurring natural hazard underpinning nationwide flood risk management (FRM) policy and social concerns in Canada, it is mostly unknown which population subgroups are highly vulnerable to flooding, where are the hotspots of social vulnerability to flood hazards, and whether groups of racial/ethnic minorities and socioeconomically vulnerable populations are disproportionately affected by flooding across Canada. Assessing socioeconomic vulnerability indicators to flood hazards and identifying their disparate relations to flood exposure help policymakers understand which racial/ethnic and socioeconomic groups are inequitably exposed to flooding. This approach better assists in making evidence-informed and risk-based decisions, which will help fight racial discrimination and redress harm due to environmental injustice by developing a socially equitable flood management policy. Social equity considerations about flood management policies, programs, and legislations are consistent with the Government of Canada’s commitment to implementing “Gender-based Analysis Plus (GBA+)” in decisions and developing the National Strategy to Redress Environmental Racism Act that helps address differential impacts of hazards on people of all genders and diverse groups of socio-economic, ethnic, and cultural groups/communities. This dissertation addressed several gaps in the Canadian literature on socioeconomic vulnerability to flooding and the distributive environmental justice analysis concerning differential exposure to flood hazards of people and places. It evaluated various spatial and non-spatial methodologies for assessing flood-related environmental inequity. The research has asked three sets of integrated research questions that jointly reflect the overall goal of analyzing social equity dimensions of flood risk management in Canada, including: (1) What are the significant socioeconomic drivers of social vulnerability to flood hazards in Canada? Where are socially vulnerable neighbourhoods geographically concentrated in Canada? (2) How exposed are residential properties to flood hazards across Canada? Do socioeconomic vulnerability and flood exposure of residential properties vary or concentrate spatially by geographic boundaries (e.g., census tracts, census metropolitan areas, and provinces/territories)? Where are the hotspots of flood risk, and which neighbourhoods are at an elevated risk of flooding and highly vulnerable to flood hazards? (3) Are certain socially vulnerable groups, including women, the elderly, lone-parent households, people with disabilities, visible ethnic minorities, Indigenous peoples, and individuals of lower socioeconomic status, inequitably exposed to flood hazards in Canada? Are relationships between Canadians’ socio-demographic characteristics and residential exposure to flood risk spatially heterogeneous? Are Canadians likely to experience environmental injustices or systemic social inequities through differential exposure to flood risk? In answer to the first set of questions, the research developed a national-scale socioeconomic status (SES) index for Canadians to measure relative social vulnerability across census tract (CT)-level neighbourhoods. Building on the literature of social vulnerability to flood hazards and flood-related EJ research (J. Chakraborty et al., 2014; Collins et al., 2017; Susan L. Cutter et al., 2003; Grineski et al., 2015; Messer et al., 2006; Oulahen, Shrubsole, et al., 2015), a wide range of 49 social vulnerability indicators were considered from six main areas, including: • Special needs populations and their coping ability. • Household or family arrangement. • Race/ethnicity status. • Access to financial resources and social supports. • Built environment characteristics of homes. • Language, gender, age, education, occupation categories, and gender-based intersectional labour force characteristics. Principal Component Analysis (PCA) on those indicators revealed 35 of the 49 census-based variables as significant representatives of social vulnerability drivers in Canada. The geographic concentration of vulnerability was delineated through geographical information system (GIS)-based choropleth mapping of SES index scores across CTs. Racial or ethnic groups were found to be among the most socially vulnerable groups in Canada, consistent with the extant environmental justice literature. Large census metropolitan areas (CMA) were substantially less socially vulnerable than their smaller counterparts. Social vulnerability was mostly concentrated in urban areas across Canada, and Atlantic Canada provinces were considerably more socioeconomically vulnerable than Western Canada and Central Canada provinces. This dissertation provided the first nationwide and comprehensive flood risk assessment by leveraging data on flood hazards, social vulnerability, and exposure of residential properties to answer the second set of questions presented above. Flood hazard exposure analysis captured the percentage of residential properties within a CT exposed to any of pluvial (surface water), fluvial (riverine), or storm surge (coastal) flooding in a 100-year return period (with or without accounting for fluvial flood defenses). The extent of flood risk and geographic concentration of risk hotspots were identified using GIS by determining most flood vulnerable neighbourhoods, where very high social vulnerability coincided with very high flood exposure. The findings suggested that Ontario and Québec had the highest number of CTs among all provinces, revealed as “at-risk” areas of flooding (i.e., 66% of the total 5721 CTs), regardless of accounting for fluvial-flood defenses. The results indicated most of the CMAs or urban regions in Central Canada and Western Canada were geographically concentrated in flood-disadvantaged areas that were susceptible to ‘high - very high’ flood risk, while fluvial-flood defense was overlooked. Population subgroups and residential properties in 18 of the 5721 CTs, over nine CMAs, were detected with very high flood risk. Four CTs in Chilliwack, BC, and Windsor, ON CMAs, were nationally recognized as having the highest flood risk. To answer the third set of questions, the dissertation investigated the environmental justice hypothesis that socioeconomically disadvantaged and visible minority population subgroups disproportionately inhabit flood zones. The dissertation also demonstrated the value of a geographically weighted regression (GWR) approach in environmental equity research to understand and examine spatial heterogeneity in exposure to flood hazards that support statistically valid analyses about the spatial relationships between flood exposure and racial, ethnic, and socio-demographic characteristics. Consistent with the environmental equity literature, the dissertation concluded that socially vulnerable residents are the predominant occupants of inland flood zones, and flood-related socioeconomic inequities are non-stationary as they vary across Canada. The research found certain vulnerable groups, such as females, lone-parent households, Indigenous peoples, South Asians, the elderly, other visible minorities, and economically insecure residents, located at a higher risk of flooding in Canadian neighbourhoods. Inland flood risk, both fluvial and pluvial, is of more significant concern for Canada as socioeconomically deprived residents disproportionately inhabit inland flood zones more than coastal flood zones. The dissertation provided several methodological contributions to advancing scholarly knowledge in the fields of social vulnerability to environmental hazards, environmental justice (EJ), and social equity implications of flood risk, including: 1. It filled a gap of national-scale scholarly research on social vulnerability analysis by developing an SES index for Canada based on a statistically valid and empirically robust methodology of PCA for dimensionality reduction in the dataset. 2. It critically deconstructs and presents a comprehensive flood risk assessment methodology by combining social vulnerability, exposure, and flood hazards data sets at the national scale to pinpoint hotspots of flood risk across Canadian neighbourhoods. 3. It advanced the quest for the most appropriate methodological framework to analyze social and spatial inequities in exposure to flood hazards after considering spatial effects. 4. It provided a unique, nationwide, quantitative EJ study and analyzed spatial heterogeneity in flood risk exposure across Canada. The results of this dissertation inform risk-based flood hazard management policies that are consistent with the Rawlsian distributive justice principle, that is, to help those most flood disadvantaged neighbourhoods first. The results are of interest to emergency managers who design policies that improve flood resilience to – at the very least - avoid approaches that exacerbate pre-existing environmental injustices (e.g., rendering inequitable flood relief or recovery resources to low-income households and renters). The analysis performed in the thesis is critically important to detect flood-vulnerable racial/ethnic subgroups and geographical regions in Canada, where disaster and emergency management resources are needed most for preparedness, response, and recovery. This thesis provides a solid foundation for prioritizing public investment in flood management policies and decisions that support GBA+, social justice as fairness, and vulnerability-based environmental equity principles in emergency management and disaster risk reduction. The findings should foster critical discussions involving governments at various levels, academia, regional scientists, and policymakers seeking data-driven and evidence-based solutions to disaster-related problems by addressing systemic social inequities and GBA+ in decisions.
Keywords: Flood Risk Management; Environmental Justice; Socioeconomic Status; GIS-based Flood Risk Assessment; Flood Exposure; Geographically Weighted Regression; Spatial Heterogeneity; Gender-based Analysis Plus (GBA+); Environmental Racism; Systemic Flood Disadvantage; Geographic Flood Disadvantage; Systemic Social Inequities; Socioeconomic Vulnerability; Canada; Environmental Equity; Flood Risk Maps; Social Vulnerability Index (SoVI); Principal Component Analysis; Geographically Weighted Logistic Regression; Spatial Regression Modeling; Simultaneous Autoregressive Models